2012
DOI: 10.1177/1533317512440493
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Cognitive Stimulation in Alzheimer Disease. The GAIA Project

Abstract: Several data suggest that physical activity and cognitive stimulation have a positive effect on the quality of life (QoL) of people with Alzheimer's disease (AD), slowing the decline due to the disease. A pilot project was undertaken to assess the effect of cognitive stimulation, physical activity, and socialization on patients with AD and their informal caregiver's QoL and mood. Fourteen patients with AD were randomly divided into active treatment group and control group. At the end of treatment, a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 35 publications
2
67
0
7
Order By: Relevance
“…Stability of scores or an attenuation of decline was reported in six group studies (Arkin, 2007;Graessel et al, 2011;Ibarria et al, 2016;La Rue et al, 2015;Maci et al, 2012;Viola et al, 2011). Two group studies, Serda`i Ferrer and del Table 6.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Stability of scores or an attenuation of decline was reported in six group studies (Arkin, 2007;Graessel et al, 2011;Ibarria et al, 2016;La Rue et al, 2015;Maci et al, 2012;Viola et al, 2011). Two group studies, Serda`i Ferrer and del Table 6.…”
Section: Resultsmentioning
confidence: 92%
“…Onor et al (2007) reported that socialization itself can lead to improvements, and 'programs that take a more holistic approach to the individual are more effective than those focusing on cognitive rehabilitation alone' (p. 270). Maci et al (2012) echoed this with their integrated approach of CS, physical activity and socialisation to slow down affective decline and reduce carer burden.…”
Section: Discussionmentioning
confidence: 99%
“…A program of therapeutic education for patients and caregivers improve the quality of life [65]. Finally, multicomponent programs have been shown to improve apathy, anxiety, depression, and quality of life [66].…”
Section: Discussionmentioning
confidence: 99%
“…Toutefois, ces interventions rapportent des effets positifs (Tableau 1) sur les symptômes dépressifs, l'humeur [40], le niveau global de cognition, les activités de vie quotidienne [40,41] et les performances physiques [40][41][42][43]. Seulement deux études chez les patients Alzheimer ont contrôlé spécifiquement l'intensité d'exercice pour stimuler de manière intense la fonction cardiorespiratoire [44,45] (c.-à-d., 70 % de la FC maximale et 70 % de la FC de réserve). Ces études rapportent des améliorations significatives sur les différentes fonctions cognitives [46,47] et sur l'efficacité de la marche [47].…”
Section: Activité Physique Régulière Aérobie Et Environnement Enrichiunclassified
“…entraînement en groupe). Ces études rapportent, chez des patients Alzheimer, des effets positifs sur l'humeur [44], l'anxiété, l'apathie, la qualité de vie [45], la dépression et les aptitudes physiques [44,49]. De plus, ces interventions mixtes freineraient le déclin cognitif [49].…”
Section: Activité Physique Régulière Aérobie Et Environnement Enrichiunclassified